DAMPAK DUKUNGAN SOSIAL TERHADAP KESEHATAN MENTAL PENYANDANG DISABILITAS - Rahmadi, M. Agung; Nasution, Helsa; Mawar, Luthfiah; Sari, Milna (Counseling For All : Jurnal Bimbingan dan Konseling, 2024)
This study analyzes the impact of social support on the mental health of individuals with disabilities in Indonesia, involving 250 participants aged 18 to 65 years. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS) and the Depression Anxiety Stress Scale (DASS-21). Multiple regression analysis results indicate that social support significantly contributes to improved mental health (β = -0.42, p < .001 for depression; β = -0.36, p < .001 for anxiety; β = -0.39, p < .001 for stress). Family support emerged as the strongest predictor, showing a negative correlation with depression (r = -0.51, p < .001) and anxiety (r = -0.43, p < .001). These findings underscore the critical importance of social support for the mental health of individuals with disabilities. Additionally, the moderation analysis by age indicates that social support has a more substantial impact on older individuals with disabilities (β = -0.14, p < .05). These findings align with the research by Tough et al. (2017) and Santini et al. (2015), emphasizing the significance of various forms of social support for individuals with disabilities in Indonesia. The study also highlights the understanding of the Indonesian cultural context, which remains discriminatory toward individuals with disabilities, and addresses the phenomenon of neglect regarding the mental health care of this population, which represents 6.7% of the national population. Therefore, the results of this study are expected to fill the existing literature gap by providing empirical evidence for the necessity of social support interventions that can significantly enhance the mental health of individuals with disabilities.